Effect of apoE on triglyceride emulsion interaction with hepatocyte and hepatoma G2 cells. - B Oswald; S Quarfordt (Journal of Lipid Research, 1987)
The uptake and internalization of a triglyceride emulsion by rat hepatocytes in culture less than 24 hr was either inhibited or uninfluenced by apoE. ApoE significantly increased the uptake of these emulsions in later cultures. Specific low density lipoprotein (LDL) binding was similar for hepatocyte monolayers prior to and after 24 hr. Rat hepatocytes in culture for 2 days, which were treated with collagenase, detached and then replated within 1 hr and were apoE-responsive in 2 hr. Heparin inhibited the apoE stimulation in both hepatocytes and hepatoma monolayers. Heparin wash of hepatocytes or hepatoma cells incubated with apoE-[14C]triolein emulsions at 4 degrees C resulted in a considerable loss in radiolabeled cell lipid. A similar wash after 37 degrees C incubations produced little loss suggesting internalization. Hepatocytes had lower affinity but similar apoE-emulsion binding capacity compared to hepatoma cells. Triolein emulsions with apoE were significantly more rapidly metabolized by the hepatocyte than unsupplemented emulsions. The apoE-mediated hepatocyte lipid uptake was inhibited by apoC proteins. High molar ratios of free fatty acid/albumin also suppressed hepatocyte apoE-mediated lipid uptake. Both rat high density lipoprotein (HDL) and LDL inhibited with a potency directly related to their content of apoE. Human LDL and HDL without apoE also inhibited the interaction with less potency than the rat lipoproteins. Human HDL inhibition was diminished after removal of apoC proteins.